PENERAPAN PRODUK GREEN ECONOMY PADA PROGRAM WIRAUSAHA MUDA BERBASIS RAMAH LINGKUNGAN DI MAN 2 PANGANDARAN - Dadah Jubaedah; Siti Saadah; Dety Mulyanti (Jurnal Abdimas Sang Buana, 2022)
The Green Economy Implementation Program in the Environmentally Friendly Young Entrepreneurs Program at MAN 2 Pangandaran is a community service program (PKM) through empowerment for students that aims to develop an entrepreneurial spirit for groups of students through environmentally friendly products. Environmental issues to date have become an important concern for the whole world along with the many problems that threaten the human environment such as global warming, depletion of the ozone layer, air, water and soil pollution. The importance of implementing the green economy as a form of awareness for students at MAN 2 Pangandaran is increasingly being carried out as a long-term program. Schools can be a comfortable and dynamic vehicle and system for students to develop good knowing, good filling, and good acting about environmentally friendly programs. This PKM program is carried out on MAN 2 Pangandaran students who have good potential and skills. The implementation method developed in this program is an extension and training method including technical training and non-technical training (knowledge transfer, skills transfer and technology transfer). The results of environmentally friendly products produced by students are flower pots made of towels, plates made of wood/rattan (hoe), photo figures and pencil cases. Keyword: Green Economy, Entrepreneurship, Environmentally Friendly Program